2017
DOI: 10.1111/gbi.12223
|View full text |Cite
|
Sign up to set email alerts
|

Identification, distribution, and quantification of biominerals in a deciduous forest

Abstract: Biomineralization is a common process in most vascular plants, but poorly investigated for trees. Although the presence of calcium oxalate and silica accumulation has been reported for some tree species, the chemical composition, abundance, and quantification of biominerals remain poorly documented. However, biominerals may play important physiological and structural roles in trees, especially in forest ecosystems, which are characterized by nutrient-poor soils. In this context, our study aimed at investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Although other studies verifi ed the presence of P, K, Mg, and S in crystals, some plant species (i.e., Piper arboreum var. arboreum, P. callosum, P. tuberculatum, Acacia robeorum, Acacia stipuligera, Acacia stellaticeps, and Fagus sylvatica) have high concentrations of these elements (SILVA et al, 2014, HE et al, 2014, KRIEGER et al, 2017. Although Al was detected in all analyzed crystals (Table 3), one of the needle crystals from the -K treatment was comprised of 2.79% Al.…”
Section: Crystal Formation and Precipitation Of Elementsmentioning
confidence: 95%
See 2 more Smart Citations
“…Although other studies verifi ed the presence of P, K, Mg, and S in crystals, some plant species (i.e., Piper arboreum var. arboreum, P. callosum, P. tuberculatum, Acacia robeorum, Acacia stipuligera, Acacia stellaticeps, and Fagus sylvatica) have high concentrations of these elements (SILVA et al, 2014, HE et al, 2014, KRIEGER et al, 2017. Although Al was detected in all analyzed crystals (Table 3), one of the needle crystals from the -K treatment was comprised of 2.79% Al.…”
Section: Crystal Formation and Precipitation Of Elementsmentioning
confidence: 95%
“…Advanced microscopy and spectroscopy techniques have allowed for a more comprehensive assessment of the elemental composition of plant tissues (DINH et al, 2015;KRIEGER et al, 2017). In the evaluation of elemental accumulation, studies have concentrated on the elemental distribution in different tissues and plant cells (CONN; GILLIHAM, 2010) including crystals (HE et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Krieger et al (2017) recently showed that Si in deciduous trees (European beech, Fagus sylvatica and sycamore, Acer pseudoplatanus) generally precipitates as a thin layer (< 0.5 µm) around the cells, especially in roots and bark. These small-scale phytogenic Si were demonstrated to influence various soil and plant processes (Meunier et al, 2017;Puppe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high Si content of fine roots (Krieger et al, 2017;Maguire et al, 2017) and their rapid turnover in forest ecosystems (approximately 1 year in beech forests in Europe; Brunner et al, 2013), we hypothesized that fine roots could significantly contribute to the input of BSi into the soil.…”
Section: Introductionmentioning
confidence: 99%